Evidentiality and Raising to Object as A′‐Movement: A Romanian Case Study. (7th July 2016) - Alboiu, Gabriela; Hill, Virginia
Abstract: Romanian displays a construction in which the subject of an embedded indicative clause surfaces with accusative form in the matrix clause. This resembles Exceptional Case Marking (ECM) and occurs with matrix verbs of knowledge and perception. We argue that: (i) such derivations arise from Raising to Object (RtoO) across the phasal indicative CP; (ii) RtoO in Romanian is an instance of A′‐movement with A‐movement effects derived from the v‐related nature of the A′‐Probe; and (iii) the trigger for movement is related to a shift in evidentiality rather than Case requirements.